2019
DOI: 10.1111/jan.13982
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and predictors of dating violence among nursing and midwifery students

Abstract: Aims:To determine the prevalence and predictors of victimization and perpetration of dating violence among nursing and midwifery students. Design:A cross-sectional study design. Methods:The sample consisted of nursing and midwifery students (N = 603) at the largest state university in southeastern Turkey. Data were collected with a validated, investigator-designed survey instrument between September 2015 and January 2016.Findings: Most participants had been exposed to dating violence. Jealousy, controlling beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
(91 reference statements)
1
14
0
Order By: Relevance
“…This shows that a number of students experienced psychological violence which results in the disruption of sleep duration. This is in line with the results of a previous study which reported that their DV respondents experienced fear, sadness, and depression to the point of unable to concentrate and sleep due to the traumatic events [16,[25][26]. The results of an interview with one of the respondents who experienced psychological violence revealed that the victim experienced psychological pressure and felt less confident, depressed, and burdened by the experience.…”
Section: Discussionsupporting
confidence: 90%
“…This shows that a number of students experienced psychological violence which results in the disruption of sleep duration. This is in line with the results of a previous study which reported that their DV respondents experienced fear, sadness, and depression to the point of unable to concentrate and sleep due to the traumatic events [16,[25][26]. The results of an interview with one of the respondents who experienced psychological violence revealed that the victim experienced psychological pressure and felt less confident, depressed, and burdened by the experience.…”
Section: Discussionsupporting
confidence: 90%
“…For example, some types of psychological violence, such as humiliation or coercion, usually goes unnoticed by victims unless their signs are very evident [ 20 22 ]. For young adults, it is also common to believe in certain myths of romantic love, assuming, for example, that it is normal to suffer for love [ 17 ], or that controlling behaviors and jealousy are part of falling in love [ 20 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of preventing IPV is being highlighted by this study because psychological violence within relationships may lead to worse situations and become a significant contemplation of physical violence occurrence in future relations (Machado et al, 2014). It was a worry when some harmful psychological behaviors were not considered violent acts such as jealousy, yelling, and restricting resources (Kisa & Zeynelog % lu, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Before administering the questionnaire, the ethical approval was granted by Universiti Sains Malaysia Human Research Ethics Committee (HREC) (USM/JEPeM/19110807). Single proportion formula was used to calculate the sample size, 71% proportion of young adults have positive perceptions towards IPV, added with 20% estimated non-response rate, end with estimated sample size calculated was 405 (Kisa & Zeynelog % lu, 2019).…”
Section: Study Samplementioning
confidence: 99%